Tissue-specific effector functions of innate lymphoid cells - Björkström, Niklas K (Blackwell Science Inc, 2013)
Innate lymphoid cells (ILCs) is the collective term for a group of related innate lymphocytes, including natural killer (NK) cells and the more recently discovered non-NK ILCs, which all lack rearranged antigen receptors such as those expressed by T and B cells. Similar to NK cells, the newly discovered ILCs depend on the transcription factor Id2 and the common γ-chain of the interleukin-2 receptor for development. However, in contrast to NK cells, non-NK ILCs also require interleukin-7. In addition to the cytotoxic functions of NK cells, assuring protection against tumour development and viruses, new data indicate that ILCs contribute to a wide range of homeostatic and pathophysiological conditions in various organs via specialized cytokine production capabilities. Here we summarize current knowledge on ILCs with a particular emphasis on their tissue-specific effector functions, in the gut, liver, lungs and uterus. When possible, we try to highlight the role that these cells play in humans.